Pengenalan Media Pembelajaran Quizizz Bagi Guru SDN 1 Sentul Jombang - Mochammad Syafiuddin Shobirin; Anggi Indah Yuliana; M Ryan Hidayatulloh; Mei Listikawati; Yessita Puspaningrum (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
The online learning system in the COVID-19 pandemic has the weakness of limited ability to realize equitable distribution of learning facilities in Indonesia. Therefore, community service activities in the form of introducing the Quizizz learning media were carried out with SDN 1 Sentul teachers and local religious content teachers in Tembelang District. This community service activity is carried out from October to November 2021 which is located at SDN 1 Sentul, Sentul Village, Tembelang District, Jombang Regency. The stages in this activity are observation; material design; and the introduction of Quizizz learning media. The results of the activities showed that (1) Quizizz learning media attracted students' interest in learning; (2) Quizizz learning media is a variation of learning media; (3) Quiziz learning media can make it easier for teachers to convey material and input values. The obstacle in this activity is the internet network which is less stable.